Analisis Kontribusi Teknologi pada Industri Susu Pasteurisasi di KUD â€œDauâ€ Malang - Sunarharum, Wenny B. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2004)
Technology is one of key role in developing many industries but its contribution is different among the types and locations of industries. Aim of this research is to analize the aspect of technological contents in pasterurized milk industry at KUD DAU Malang.Â Technometric approach was used to measure Technological Coefficient Centribution (TCC).Â The result showed TCC score was 0.369 (scale 0 to 1). Inforware as one of Technologyâ€™s Component gave the score of 0.380.Â This is the greatest contribution in the value added of pasteurized milk, followed by humanware, technoware, and argaware. It can be concluded that Technological Contribution in KUD DAU was not considered high enough and need to be improved. Keywords : pasteurized milk industry, Technometric approach, Technology Contribution Coefficient